Connecting Aquaculture to the Internet of Things A Model for Aquaculture Quality and Water Preservation - AlMetwally, Saif; Mourad, Mohamed H.; Hassan, Mohamed K. (Journal of Industrial Engineering & Management Research, 2024)
Water, food, and energy are vital resources for humanity. This work introduces a system design, results, economic model, and solutions for an aquaculture smart system enabling monitoring and control of fish farming tanks’ water quality. Reducing water usage, producing better quality food, reducing production costs, and optimizing the aquaculture water quality are the results of this research. System design and an economic model are presented together with the system data of the working prototype including calibration, verification, and validation. A mobile application was developed to observe and regulate the quality parameters of water. This research implements Internet of Things tools to monitor and control the parameters through embedded sensors for temperature, turbidity, pH, and water level/consumption. The system automatically intervenes online depending on the value of the measured parameters through a controller-predefined logic to set the parameters within acceptable limits. The verification and validation of results are presented by comparing the online and offline data measurements. The work also presents an economic analysis comparing financial indicators for traditional and smart farms including sensitivity analysis. The system implementation leads to a reduction in water consumption by 42%, and an 8% utilization of the actuators, leading to very low energy consumption and longer actuators’ useful life. The system also produces higher-quality fish satisfying the EU standards due to the controlled living environment.